Superabsorbent, Breathable Graphene Oxide-Based Nanocomposite Hydrogel as a Dense Membrane for Use in Protective Clothing. Issue 2 (22nd January 2019) - Gorji, M.; Karimi, M.; Mashaiekhi, G.; Ramazani, S.
ABSTRACT: This study examines the synthesis, fabrication and characterization of poly acrylamido methyl propane sulfonic acid (PAMPS)/graphene oxide (GO) nanocomposites. PAMPS-GO nanocomposite hydrogel was synthesized by radical initiated polymerization and its swelling properties, water vapor permeability (WVP), and stress-strain behavior were evaluated. The swelling behavior of hydrogel nanocomposites were improved at the presence of 0.2 wt% GO, as confirmed by water uptake experiments. It should be noted that as GO loading increased, so did the WVP of the hydrogel. The stress-strain test also revealed that the incorporation of just 0.1% of GO raised the tensile strength and young modulus of the hydrogels by 42% and 37% respectively. These fabricated dense membranes can have applications in protective clothing and wound dressing. Graphical Abstract: GRAPHICAL ABSTRACT